Pomegranate juice induced cell cycle arrest and apoptosis through mitochondria pathway in human lung adenocarcinoma cells - Abdul Ghani, Radiah; Nik Abdul Malek, Nik Nurasyikin; Mohd. Ashari, Noor Suryani; Abdullah, Nor Zamzila (Science Publishing Corporation, 2018)
Lung cancer is the most common type of cancer which the mortality rate increases year by year. Therapeutic drugs could not control the progression of cancer and it contributes to the side effects in normal cells. Thus, an alternative strategy using natural product becomes a focus today. Punica granatum, known as pomegranate has demonstrated the anti-proliferative effect in A549 cells. To further confirm its efficacy, this study aimed to investigate the type of cell death and its pathway in A549 cells. Propium Iodide staining was applied to de-termine the cell cycle profile changes induced by this juice. The determination of type of cell death was done using Annex in-V staining and later will be analyzed using flow cytometer. The pathway to apoptosis was investigated by determining the caspase- 3, 8 and 9 activi-ties. The findings were supported by mitochondrial membrane permeability assay and cytochrome c release detection which were later analyzed using flow cytometer. This study revealed that pomegranate juice induced cell cycle arrest at G0/G1 phase and apoptosis through intrinsic pathway following 24 h treatment. Pomegranate juice caused loss of mitochondrial membrane permeability after 48 h (p<0.05) exposure and a release of cytochrome c in cytosol after 24 h (p<0.05) and 48 h (p<0.01) exposure in treated A549 cells. In caspases analysis, it was showed that there was activation of caspase-3 following 72 h (p<0.01) treatment and caspase-9 after 48 (p<0.01) and 72 h (p<0.05) exposure in treated A549 cells. It can be concluded that pomegranate juice able to cause A549 cell growth inhibition by inducing cell cycle arrest and apoptosis through mitochondrial pathway.